PENGARUH KEBIJAKAN HUTANG, PERENCANAAN PAJAK TERHADAP MANAJEMEN LABA - Muhammad Hamzah Fauzan; Benarda, S.P., M.M. (Yayasan Sahabat Cendekia Jaya, 2024)
Purpose. This research aims to examine the influence of debt policy and tax planning on earnings management. Debt policy is measured by the debt to asset ratio, tax planning is measured by the tax retention ratio and earnings management is measured by market value of equity. Methods. This research is a quantitative research type. The research sample was 27 food and beverage sector companies listed on the Indonesia Stock Exchange, which were selected using a purposive sampling method in the 2018-2022 research period. Data were analyzed using panel data regression. Results. Based on the research results, it can be concluded that debt policy, and tax planning influences earnings management. Implications. Debt policy influences earnings management, tax planning influences earnings management and debt policy and tax planning simultaneously influence tax avoidance. Keywords: Debt Policy, Tax Planning, Profit Management.